Osservazioni sul patrimonio stabile degli enti canonici. Al crocevia fra disciplina civile, diritto canonico e prassi (Stato, Chiese e pluralismo confessionale, 2024)
Observations on the stable patrimony of canonical bodies. At the crossroads between civil discipline, canon law and regulation practiceABSTRACT: The aim of the paper is to reflect, starting from the renewed interest of doctrine in relation to the canonical concept of "stable patrimony", on the theoretical and applicative profiles connected to it. In particular, adequate attention is paid to civil law profiles and to the problems arising in application practice.SOMMARIO: 1. La riscoperta del patrimonio stabile - 2. La prospettiva civilistica - 3. Il patrimonio stabile come strumento operativo - 4. Questioni aperte prassi applicativa - 4.1. - Due criteri che devono presiedere gli atti di legittima assegnazione - 4.2. - Profili pubblicitari dell’atto di legittima assegnazione - 5. Considerazioni conclusive.